Mechanical Force Activates the Light-Dependent Channels Trp and Trpl in Excised Patches from the Rhabdomere of Drosophila Photoreceptors - Melo-Hurtado, F; Caballero-Alvial, L (Elsevier Ltd, 2024)
Drosophila phototransduction in light-sensitive microvilli involves a metabotropic signaling cascade. Photoisomerized rhodopsin couples to G-protein, activating phospholipase C, which cleaves phosphatidylinositol bisphosphate (PIP2) into inositol trisphosphate, diacylglycerol (DAG) and a proton. DAG is converted into phosphatidic acid by DAG-kinase and metabolized to L-linoleoyl glycerol (2-LG) by DAG-lipase. This complex enzyme cascade ultimately opens the light-dependent transient receptor potential channels, TRP and TRPL. PIP2, DAG, H+ and 2-LG are possible channel activators, either individually or combined, but their direct participation in channel-gating remains unresolved. Molecular interaction with the channels, modification of the channels’ lipid moiety and mechanical force on the channels by changes in the membrane structure derived from light-dependent changes in lipid composition are possible gating agents. In this regard, mechanical activation was suggested, based on a rapid light-dependent contraction of the photoreceptors mediated by the phototransduction cascade. Here, we further examined this possibility by applying force to inside-out patches from the microvilli membrane by changing the pressure in the pipette or pulling the membrane with a magnet through superparamagnetic nanospheres. The channels were opened by mechanical force, while mutant lacking both channels was insensitive to mechanical stimulation. Atomic Force Microscopy showed that the stiffness of an artificial phospholipid bilayer was increased by arachidonic acid and diacylglycerol whereas elaidic acid was ineffective, mirroring their relative effects in channel activity previously observed electrophysiologically. Together, the results are consistent with the notion that light-induced changes in lipid composition alter the membrane structure, generating mechanical force on the channels leading to channel opening. © 2024 IBRO